Все о Пеппи Длинныйчулок: [сказочные повести] / А. Линдгрен - Линдгрен Астрид Анна Эмилия (АСТ, 2012)
Экземпляры: ф.20 (20160602) / Инвентарный номер: 56954 / Цена: / Сис.шифр: 84(4Шве)-4 / Авт.знак: Л 59 / ГРНТИ: 17.82.31 / ББК: 84(4Шве)-4